Experimental performance analysis of an infrared heating system for continuous applications of drying - Hany S. El-Mesery; Hao Huang; Zicheng Hu; Mohammad Kaveh; Mohamed Qenawy (Case Studies in Thermal Engineering, 2024)
One feasible approach for enhancing material quality and expediting the dehydrating procedure is using infrared radiation to provide heat. The impact of infrared power (0.130–0.341 W/cm2), airflow (0.5–1.5 m/s), and slice thickness (2–6 mm) on mass transfer, drying kinetics, colour, shrinkage, and rehydration ratio conditions. During the process, the dried samples' initial moisture content of 86.7 % was decreased to 11 % (w.b.). Eleven statistical factors were used to compare eleven alternative mathematical models. The results of regression analysis indicated that the Midilli et al. model best describes the drying behaviour in both techniques. The outcomes exhibited that the drying period rose at airflow and thickness but decreased with intensity. While the shrinkage ratio increased and declined with air velocity, the rehydration ratio grew and dropped with increasing infrared radiation intensity and airflow. As the intensity and airflow increased, there was a noticeable increase in the overall colour difference between slices of fresh and dry apples. The outcomes of this investigation will offer a further understanding of the ideal drying settings to create apple slices for snacking or other culinary purposes.